Attaching and effacing enteropathogenic Escherichia coli O18ab invades epithelial cells and causes persistent diarrhea. - Scaletsky, I C (1996)
A case of persistent diarrhea following Escherichia coli O18ab gastroenteritis is reported. Electron microscopy of a biopsy of the small intestine showed effacement of the brush border, attachment of bacteria to the epithelial cells with pedestal formation, and bacteria within the enterocytes. The bacterial isolate was an enteropathogenic E. coli isolate which did not contain the adherence factor (EAF) but possessed the attaching-effacing eae gene, was able to invade HeLa cells in a gentamicin invasion assay, and also invaded rabbit intestinal cells. Results suggest that E. coli organisms of the O18ab serotype may cause diarrhea by an as yet unknown pathogenic mechanism, involving attaching to and effacing of enterocytes followed by invasion of the epithelial cells.